1983
DOI: 10.1038/304602a0
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus early region 1A enables viral and cellular transforming genes to transform primary cells in culture

Abstract: The polyoma virus middle-T and the T24 Harvey ras1 genes are individually unable to transform primary baby rat kidney cells. Adenovirus early region 1A provides functions required by these genes to transform primary cells following DNA-mediated gene transfer. These results suggest that separate establishment and transforming functions are required for oncogenic transformation of primary cells in culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
675
2
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,226 publications
(705 citation statements)
references
References 31 publications
25
675
2
3
Order By: Relevance
“…There are a number of similarities between the myc-and Ela genes, including a nuclear localization of their gene products and an ability of each to cooperate with ras oncogenes in the transformation of primary cells (Yee et al, 1983;Land et al, 1983;Ruley, 1983;Persson and Leder, 1984). Other evidence suggests that the c-myc protein, like Ela, can enhance the transcription of other genes (Kingston et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of similarities between the myc-and Ela genes, including a nuclear localization of their gene products and an ability of each to cooperate with ras oncogenes in the transformation of primary cells (Yee et al, 1983;Land et al, 1983;Ruley, 1983;Persson and Leder, 1984). Other evidence suggests that the c-myc protein, like Ela, can enhance the transcription of other genes (Kingston et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Ras cooperation assay performed in primary rat embryo ®broblasts (REFs) (Land et al, 1983;Ruley, 1983), we previously showed that Bin1 inhibits malignant transformation by c-Myc in a MBDdependent manner . To de®ne other regions required, REFs were transfected with expression vectors for Myc, oncogenic Ras, and Bin1 or Bin1 deletion mutants, and transformed cell foci were scored 2 weeks later ( Figure 5).…”
Section: Bin1 Inhibits Malignant Cell Transformation By Multiple Mechmentioning
confidence: 99%
“…E1A CR2 binds retinoblastoma (RB) family members, de-repressing E2F transcription factors and inducing cell cycle progression. However, E1A-expressing cells eventually degenerate in soft agar and do not form colonies (Ruley, 1983). This is largely due to E1A's ability to induce p53 stabilization through upregulation of Arf (de Stanchina et al, 1998), CBP/p300 binding (Grossman et al, 1998) and proteosome modification by E1A CR1 (Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%